If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 4x = 2x + 16 Reorder the terms: 3 + 4x = 16 + 2x Solving 3 + 4x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 4x + -2x = 16 + 2x + -2x Combine like terms: 4x + -2x = 2x 3 + 2x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 2x = 16 + 0 3 + 2x = 16 Add '-3' to each side of the equation. 3 + -3 + 2x = 16 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 16 + -3 2x = 16 + -3 Combine like terms: 16 + -3 = 13 2x = 13 Divide each side by '2'. x = 6.5 Simplifying x = 6.5
| -6p-7p=6-8p-8p | | -7a-6a=-7a | | x^2-x-25=5 | | x-5/3=-1/3 | | 7=3z-2 | | -2(7-8n)=-110 | | 7(2x+6)=126 | | 10(1+2k)=490 | | x+1-2=2 | | 7x-3/3x=4 | | X+112+92=180 | | y-3x-12=0 | | 8+8x-7x=x+8 | | x^2+19x+50=0 | | 4x+1=5x-9 | | x^2+19x+50= | | (6y^2-43y-20)/(y-8) | | (6n^2)+7n-3=0 | | 8^3/2^9 | | 10=2x+16 | | 8x^3/2x^9 | | 5/9p=15 | | 4+x+(-17)=9 | | -39r-2=30 | | (3x-4)(x+2)=112 | | (12x+38)=(8x+1) | | 2x^2+3x+1=2x^2+9x+9-14 | | sinx+sqrt(2)=-sinx | | y=x^3-6 | | A=4nr^2 | | 4(x+3)=5x+28 | | 8(2x-1)=-32 |